Fat containing unusual tumor of the pancreas - Barutcu, O; Cihangiroglu, M; Yildirim, T; Kayaselcuk, F; Noyan, T (Springer-Verlag, 2002)
Fat-containing pancreatic tumors are very rare. In the literature, less than ten cases of lipoma originating from the pancreas have been reported. We present a case of pancreatic lipoma in a 65-year-old woman with findings of ultrasonography, computed tomography, and magnetic resonance imaging in addition to a brief review of the literature.
Keywords: pancreas; lipoma; CT; MRI